Association of Statin Use With the In-Hospital Outcomes of 2019-Coronavirus Disease Patients: A Retrospective Study - Fan, Yongzhen; Guo, Tao; Yan, Feifei; Gong, Ming; Zhang, Xin A.; Li, Chenze; He, Tao; Luo, Huimin; Zhang, Lin; Chen, Ming; Wu, Xiaoyan; Wang, Hairong; et al. (Frontiers in Medicine, 2020)
Statins have multiple protective effects on inflammation, immunity and coagulation, and may help alleviate pneumonia. However, there was no report focusing on the association of statin use with in-hospital outcomes of patients with coronavirus disease 2019 (COVID-19). We investigated the association between the use of statins and in-hospital outcomes of patients with COVID-19. In this retrospective case series, consecutive COVID-19 patients admitted at 2 hospitals in Wuhan, China, from March 12, 2020 to April 14, 2020 were analyzed.Demographic data, laboratory findings, comorbidities, treatments and in-hospital outcomes were collected and compared between COVID-19 patients taking and not taking statins. A total of 2147 patients with COVID-19 were enrolled in this study. Of which, 250 patients were on statin therapy. The mortality was 2.4% (6/250) for patients taking statins while 3.7% (70/1897) for those not taking statins. In the mixed-effects Cox model, after adjusting for age, gender, admitted hospital, comorbidities, in-hospital medications and blood lipids, the risk was lower for mortality (adjusted HR, 0.428; 95% CI, 0.169-0.907; P=0.029), acute respiratory distress syndrome (ARDS) (adjusted HR, 0.371; 95% CI, 0.180-0.772; P=0.008) or intensive care unit (ICU) care (adjusted HR, 0.319; 95% CI, 0.270-0.945; P=0.032) in the statin group versus the non-statin group. After propensity score-matched analysis based on 18 potential confounders, a 1:1 matched cohort (206:206) was created. In the matched cohort, the Kaplan-Meier survival curves showed that the use of statins was associated with better survival (P=0.025). In a Cox regression model, the use of statins was associated with lower risk of mortality (unadjusted HR, 0.254; 95%CI, 0.070-0.926; P=0.038), development of ARDS (unadjusted HR, 0.240; 95%CI, 0.087-0.657; P=0.006), and admission of ICU (unadjusted HR, 0.349; 95%CI, 0.150-0.813; P=0.015). The favorable outcomes in statin users remained statistically significant in the first sensitivity analysis with comorbid diabetes being excluded in matching and in the second sensitivity analysis with chronic obstructive pulmonary disease being added in matching. In this retrospective analysis, the use of statins in COVID-19 patients was associated with better clinical outcomes and is recommended to be continued in patients with COVID-19.